1991
DOI: 10.1063/1.105236
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nanocrystalline cubic boron nitride by microwave plasma-enhanced chemical vapor deposition

Abstract: Polycrystalline boron nitride films have been deposited using microwave plasma-enhanced chemical vapor deposition. IR absorption spectra of films deposited using NaBH4 as the boron source in NH3 and H2 gases showed absorptions which are nearly the same as the characteristic vibrational modes seen in cubic and pyrolytic boron nitrides. Films deposited at 5 Torr also showed electron diffraction patterns for pyrolytic boron nitride, turbostratic boron nitride and cubic boron nitride. At higher gas pressures, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…16,17,19 FTIR spectra of three films deposited in N 2 with and without substrate bias and nitrogen plasma are shown in Fig. 1.…”
Section: A Structural Propertiesmentioning
confidence: 99%
“…16,17,19 FTIR spectra of three films deposited in N 2 with and without substrate bias and nitrogen plasma are shown in Fig. 1.…”
Section: A Structural Propertiesmentioning
confidence: 99%
“…[8][9][10][11][12][13] BN is well known as a material which has various phases such as hexagonal, cubic, and so on with growth methods and conditions. We characterized BN films synthesized by plasma-assisted chemical vapor deposition and found that the electron emission occurred from sulfur ͑S͒-doped BN films at a low electric field.…”
Section: ͓S0003-6951͑97͒00944-3͔mentioning
confidence: 99%
“…c-BN gained its fame around the mid-twentieth century after its synthesis by Wentorf (2), who synthesised it by the high pressure and high temperature method. Since then, various material scientists have been researching on ways to synthesise in nanoscale and as thin film (3)(4)(5). c-BN is an important material because of its superior properties such as super hardness (75 GPa), high thermal stability for temperatures up to 3000 K, high thermal conductivity of about 13 W/m K, wide indirect bandgap of 6.5 eV and low dielectric constant (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%